2010
DOI: 10.1111/j.1365-2850.2010.01632.x
|View full text |Cite
|
Sign up to set email alerts
|

The characteristics, management and outcomes of people identified with mental health issues in an emergency department, Melbourne, Australia

Abstract: Although the number of mental health presentations to emergency departments is increasing as a result of the integration of psychiatric services with general services, few studies have explored the characteristics of mental health patients presenting to emergency departments in Australia. This study investigated the characteristics of, and outcomes in relation to, people presenting with a mental health problem to one large metropolitan emergency department. Data were collected from the emergency department's e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 25 publications
(75 reference statements)
4
35
1
1
Order By: Relevance
“…No study of the general patient population considered specific physical diagnoses; one included broad diagnostic categories (which showed inconsistent effects across different segments of ED LOS),14 another reported that diagnoses were included in the analysis but provided neither definition nor results 10. Analyses of specific diagnoses or symptoms were more commonly undertaken in condition-specific studies,12 28 29 31 32 34 35 38 but the results may not be relevant to other populations. Other characteristics . Of the seven American studies that considered insurance status, most found longer stays among uninsured patients8 14 17 34 38 or those without private insurance,12 and two also found longer stays among Medicaid patients;14 38 one study of non-admitted patients reported that only Medicare patients had longer LOS 19.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…No study of the general patient population considered specific physical diagnoses; one included broad diagnostic categories (which showed inconsistent effects across different segments of ED LOS),14 another reported that diagnoses were included in the analysis but provided neither definition nor results 10. Analyses of specific diagnoses or symptoms were more commonly undertaken in condition-specific studies,12 28 29 31 32 34 35 38 but the results may not be relevant to other populations. Other characteristics . Of the seven American studies that considered insurance status, most found longer stays among uninsured patients8 14 17 34 38 or those without private insurance,12 and two also found longer stays among Medicaid patients;14 38 one study of non-admitted patients reported that only Medicare patients had longer LOS 19.…”
Section: Resultsmentioning
confidence: 99%
“…No study of the general patient population considered specific physical diagnoses; one included broad diagnostic categories (which showed inconsistent effects across different segments of ED LOS),14 another reported that diagnoses were included in the analysis but provided neither definition nor results 10. Analyses of specific diagnoses or symptoms were more commonly undertaken in condition-specific studies,12 28 29 31 32 34 35 38 but the results may not be relevant to other populations.…”
Section: Resultsmentioning
confidence: 99%
“…Emergency care nurses probably have the highest exposure to psychiatric emergencies because of the nature of their work environment and patient load. Between 5% and 13% of patients admitted to EDs have a psychiatric or chemical abuse problem (Owens, Mutter, & Stocks, 2010;Shafiei, Gaynor, & Farrell, 2011). According to California Health and Safety Code 1257.8, nurses who work in EDs must have training in management of assaultive behavior.…”
Section: Discussionmentioning
confidence: 97%
“…1-4 As a result, a significant number of psychiatric patients use EDs as their main entrance into the health care system [5][6][7][8] and as a source of primary care.…”
mentioning
confidence: 99%